Judges' Decisions as a Source of Family Law: Case Studies in Indonesia and Malaysia - Kaha, Humaidi; Burhanudin, Achmad Asfi; Al Faruq, Muhammad (STAI Miftahul Ula Nganjuk, 2023)
Judges' decisions play an important role in shaping family law in Indonesia and Malaysia, especially in cases of child custody, divorce procedures, and post-divorce maintenance. This article analyses how the differences between the civil law system in Indonesia and the common law system in Malaysia affect the role of judges in determining just decisions. In addition to discussing normative aspects, this research also explores the impact of judges' decisions on society, especially women and children after divorce. The results show that in Malaysia, stronger legal mechanisms such as the Family Support Division (FSD) help ensure compliance with judges' decisions, while in Indonesia, the execution of judgements often relies on individual initiatives, leading to difficulties in the enforcement of maintenance and childcare rights. In addition, the flexibility of judges in the common law system allows for more contextual considerations in custody disputes, whereas the civil law system in Indonesia tends to be more rigid in applying written legal norms. This article recommends strengthening the mechanism of judgement execution in Indonesia to improve protection for women and children, as well as improving the consistency of judgements in Malaysia to avoid legal uncertainty. Thus, the role of judges in shaping family law can be more responsive to the needs of society.